2019
DOI: 10.5194/esurf-7-723-2019
|View full text |Cite
|
Sign up to set email alerts
|

Seeking enlightenment of fluvial sediment pathways by optically stimulated luminescence signal bleaching of river sediments and deltaic deposits

Abstract: Abstract. Reconstructing sediment pathways in fluvial and deltaic systems beyond instrumental records is challenging due to a lack of suitable methods. Here we explore the potential of luminescence methods for such purposes, focusing on bleaching of the optically stimulated luminescence (OSL) signal of quartz sediments in a large fluviodeltaic system across time and space. We approach this by comparing residual doses of sand and silt from the modern Mississippi River channel with estimated residual doses of sa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…Actually, previous investigations have demonstrated that the residual dose of modern fluvial sand samples from the middle reaches of the Yellow River are only 0.1 to 2.4 Gy, and have a large scatter, with OD values up to 90% [18,20,55]. The small residual doses of the modern fluvial sand samples are also confirmed by those of modern analogues from different rivers in the world (e.g., [56][57][58][59]). These suggest that the effect of the residual dose on the old samples from the terrace deposits in this study are insignificant.…”
Section: Reliability Of Osl Agesmentioning
confidence: 70%
“…Actually, previous investigations have demonstrated that the residual dose of modern fluvial sand samples from the middle reaches of the Yellow River are only 0.1 to 2.4 Gy, and have a large scatter, with OD values up to 90% [18,20,55]. The small residual doses of the modern fluvial sand samples are also confirmed by those of modern analogues from different rivers in the world (e.g., [56][57][58][59]). These suggest that the effect of the residual dose on the old samples from the terrace deposits in this study are insignificant.…”
Section: Reliability Of Osl Agesmentioning
confidence: 70%
“…Grall et al, 2018), accretion (e.g. Chamberlain et al, 2017), and determining the timing and pathways of active river channels (e.g. Allison et al, 2003 ;Sincavage et al, 2018).…”
Section: The Bengal Basinmentioning
confidence: 99%
“…The low formation and preservation of peat in the Bengal Basin is a direct consequence of the system's sedimentary processes and environmental conditions. Three principal factors play a role: (i) a lack of available accommodation due to the high sediment yield (Chamberlain et al, 2017); (ii) remineralization and flushing under the highly seasonal climate (Allison et al, 2003); and (iii) a lack of preservation due to laterally mobile channel belts in upstream regions of the delta (Wilson and Goodbred, 2015). Foremost, the widespread, seasonal deposition of siliciclastic sediment limits the concentrated accumulation of organic matter.…”
Section: Radiocarbon Datingmentioning
confidence: 99%
See 1 more Smart Citation
“…Incomplete reset ("bleaching") of OSL signal before deposition of quartz grains can lead to residual doses and age overestimation. However, studies about OSL signals of quartz from water-laid sediments (e.g Hu et al, 2010;Chamberlain and Wallinga, 2019). show that silt grains are relatively well-bleached and suitable for luminescence dating.…”
mentioning
confidence: 99%